THE MAIN FEAUTURES OF PEDAGOGICAL STRATEGIES ON IMPROVING THE QUALITY OF EDUCATION IN PRESIDENTIAL SCHOOLS IN UZBEKISTAN - Muminov Obidkhon Norkhujaevich (International Scientific and Current Research Conferences, 2023)
This article deals with pedagogical strategies for improving the quality of education in the Presidential schools such as vision and mission of Presidential schools and high quality of learning and teaching(HQLT); their impact on the educational process of students, consistent monitoring and management of the educational process in the Presidential schools during educational process.